Photocatalytic Oxidation of Propylene on Pd-Loaded Anatase TiO(2) Nanotubes Under Visible Light Irradiation - Li, Chen (Nanoscale Res Lett, 2016)
TiO(2) nanotubes attract much attention because of their high photoelectron-chemical and photocatalytic efficiency. But their large band gap leads to a low absorption of the solar light and limits the practical application. How to obtain TiO(2) nanotubes without any dopant and possessing visible light response is a big challenge nowadays. Orthorhombic titanic acid nanotubes (TAN) are a special precursor of TiO(2), which possess large Brunauer-Emmett-Teller (BET) surface areas and strong ion exchange and adsorption capacity. TAN can transform to a novel TiO(2) with a large amount of single-electron-trapped oxygen vacancies (SETOV) during calcination, while their nanotubular structure would be destroyed, and a BET surface area would decrease remarkably. And interestingly, SETOV can lead to a visible light response for this kind of TiO(2). Herein, glucose was penetrated into TAN by the vacuum inhalation method, and TAN would dehydrate to anatase TiO(2), and glucose would undergo thermolysis completely in the calcination process. As a result, the pure TiO(2) nanotubes with visible light response and large BET surface areas were obtained. For further improving the photocatalytic activity, Pd nanoparticles were loaded as the foreign electron traps on TiO(2) nanotubes and the photocatalytic oxidation efficiency of propylene was as high as 71 % under visible light irradiation, and the photostability of the catalyst kept over 90 % after 4 cyclic tests.